Absence of Nursing Position in the new Health Policies in Iran: A Dialogue with Nursing Scholars and Nursing Managers - Ahmad Kalateh Sadati; Mahnaz Siahi (Shiraz University of Medical Sciences, 2016)
Family physician (FP) is a suggested model for controlling Iran health system challenges such as non-communicable diseases (NCDs), mental illnesses, and HIV-AIDS besides urbanization, and elderly issues. Although FP is a legal commitment, it faces several obstacles such as lack of infrastructure, diversity of insurances, and unwillingness of senior health policy makers about it.1 As Shiraz University of Medical Sciences (SUMS) is a pilot center for implementation of FP model, the First International Conference on Family Physician with participation of Health Policy Research Center (HPRC) was conducted successfully on 27th and 28th of December 2015 in Shiraz, Iran. The main goal of this conference was developing the discourse of FP with these major subjects: 'the philosophy of FP', 'FP and medical education', 'FP and universal health coverage', 'incentive and financial system in FP', and 'evaluation of the international, national and provincial experiences in FP'. Despite presenting interesting topics in the conference, the main missing issue was the role of nursing, specifically nursing practitioner (NP), in the conference. Experiences of other countries revealed that NP has an important role in primary health care (PHC),2,3 quality of care,3 diagnosis and treatment4 in healthcare system. Moreover, International Council of Nursing believed that nursing can be effective for universal health coverage and being cost-effective in health care delivery.5 However, none of the nursing scholars and nursing managers actively participated in this conference. With respect to recent great changes in health care system in Iran, problem is not limited to this conference. Absence of community based approaches in nursing is obvious in three major health policies recently approved in Iran; they include establishing FP project in two provinces (Fars and Mazandaran) as pilot, making urban community health centers (UCHC) or Comprehensive Health Center in big cities6 and Health Sector Evolution Plan (HSEP). However, the main parts of these programs are related to PHC which needs community based approaches, but there was no any active participation of nursing groups, theoretically and practically. Sometimes the ignorance of nursing position is very precise. For instance, in the conference, it was remarked that FP's assistant will be trained on January 2016 in SUMS. Whereas Behvarz, as the most familiar discipline with nursing, has had a brilliant role in the last rural primary health care in Iran, the main question is that "Who can be better than educated nursing staff as FP's assistant?" Although ignorance of nursing position is related to approaches of policy makers, passivity of nursing scholars and nursing managers amplifies the problem. There is a big gap between policy makers and nursing on one hand and nursing scholars and nursing managers on the other hand. In this situation, nursing groups should be more sensitive to new changes such as FP, UCHC and HSEP theoretically and practically for promoting health in the community with preventive and consultative functions of NP. This approach not only helps to establish the real position of nursing but also can decrease the health system costs. This claim surely needs a clear plan. Therefore, teaching nurses according to community-based approaches, interaction between faculty of nursing and community, and conducting surveys seem necessary. Additionally, division of labor in health care system is a focal point for assigning some duties to NPs. Implementation of this idea can practically lead to repetition of the last position of Behvarz for the new generation of nursing in Iran. Today, Iran healthcare system has faced increasing costs due to changes in the patterns of illnesses, prevalence of NCDs and other mentioned problems. Utilization of expert NPs is an approach for declining the effects of such problems. Although policies ignore community- based functions in nursing, it is the responsibility of nursing scholars and nursing managers to regenerate their position in major changes.